TOURIST GUIDE TRAINING FOR PAINGAN POKDARWIS MEMBERS, NAGARI GUGUAK KURANJI HILIR PADANG PARIAMAN TOURISM VILLAGE - Novi Yanita; Yudhytia Wimeina; Azzahra Yasmine; Ferdinal Putra (Universitas Airlangga, 2023)
The aim of this community service activity is to help members of the Paingan Tourism Awareness Group (POKDARWIS) prepare themselves to become tour guides in the tourist village of Nagari Guguak Kuranji Hilir, Padang Pariaman Regency by providing training and assistance. To carry out this activity using lecture, discussion, demonstration, and simulation methods as a tour guide. More than ten people who are members of POKDARWIS Paingan Tourism Village Nagari Kuranji Hilir Padang Pariaman Regency participated in community service activities in the form of tour guide training at the home of one of the Paingan POKDARWIS members. This activity resulted in increasing the knowledge and skills of POKDARWIS Paingan members in terms of guiding tourists, especially for the Nagari Guguak Kuranji Hilir tourist village according to its tourist attractions. This can be seen from the ability of the training participants who were asked to simulate as tour guides during the activity. In addition, the service implementation team accompanied POKDARWIS members through the WhatsApp social media group to continue to provide motivation and direction to PAINGAN POKDARWIS members to improve their abilities as tour guides and provide better service to visitors to the Guguak Kuranji Hilir Tourism Village.